Selective recovery of lithium from spent lithium iron phosphate batteries: a sustainable process. Issue 13 (20th June 2018) - Yang, Yongxia; Meng, Xiangqi; Cao, Hongbin; Lin, Xiao; Liu, Chenming; Sun, Yong; Zhang, Yi; Sun, Zhi
Abstract : An effective and sustainable approach is demonstrated for selective leaching of lithium from spent lithium iron phosphate batteries. Abstract : In recent years, the recovery of metals from spent lithium ion batteries (LIBs) has become increasingly important due to their great environmental impact and the wastage of valuable metallic resources. Among different types of spent LIBs, processing and recycling the spent LiFePO4 batteries are challenging because of their relatively low extraction efficiency and recycling selectivity of valuable metal(s) and great potential for secondary waste generation. In this research, an effective and sustainable approach for selective leaching of lithium from spent LiFePO4 batteries was demonstrated. By properly adjusting or controlling the oxidative state and proton activity of the leaching solution, lithium was found to be selectively leached with a high recovery efficiency. The aluminium remained in the metallic form and iron as FePO4 in the solid residue which can be easily separated by sieving. The effects of a range of parameters ( i.e. acid concentration, initial volume fraction of the oxidant, liquid-to-solid ratio, reaction temperature and time) during lithium leaching were comprehensively investigated. The selective reaction mechanisms were clarified and the controlling step for the leaching kinetics was identified. Based on the laboratory scale results, a pilot batch process was developed and simulated. The process is found to be techno-economically feasible and environmentally friendly for recycling of spent LiFePO4 batteries using selective leaching. High purity Li2 CO3 (99.95 wt%) could be obtained with a high recovery rate. This research demonstrates the possibility of improving the metal recycling effectiveness from spent LiFePO4 batteries by incorporating the principles of green chemistry and probably contributes to the sustainability of the lithium ion battery industry.